2010
DOI: 10.1016/j.engstruct.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization and dynamic analysis of a tensegrity-based footbridge

Abstract: Tensegrity structures are spatial structural systems composed of struts and cables with pin-jointed connections. Their stability is provided by the self-stress state in tensioned and compressed members. Although much progress has been made in advancing research into the tensegrity concept, a rapid survey of current activities in engineering practice shows that much of its potential has yet to be accomplished. A design optimization study for a tensegrity-based footbridge is presented in order to further advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The deployable tensegrity footbridge is composed of four identical pentagonal ring modules connected together in a "hollow-rope" system, where the empty space in their center is used as walking space with the addition of a deck. The hollow-rope tensegrity system was found viable for a tensegrity footbridge [29,30]. However, clustered cables, spring elements and deployment were not taken into account.…”
Section: The Tensegrity-ring Footbridgementioning
confidence: 99%
“…The deployable tensegrity footbridge is composed of four identical pentagonal ring modules connected together in a "hollow-rope" system, where the empty space in their center is used as walking space with the addition of a deck. The hollow-rope tensegrity system was found viable for a tensegrity footbridge [29,30]. However, clustered cables, spring elements and deployment were not taken into account.…”
Section: The Tensegrity-ring Footbridgementioning
confidence: 99%
“…Their internal empty ring space is used as walking space with the addition of a deck. Previous work by the authors revealed that tensegrity-ring modules are viable structural systems for a footbridge application Rhode-Barbarigos et al 2010). Based on the deployability of ring modules, the structural system of the tensegrity-ring bridge can be extended for a deployable footbridge application.…”
Section: Tensegrity-ring Modules and Footbridge Applicationmentioning
confidence: 99%
“…Design optimization of the tensegrity bridge is performed using member dimensions and selfstress level as design variables following a procedure described in Bel Hadj Ali et al [28]. Struts are separated into two design groups: diagonal and intermediate struts.…”
Section: Design Characteristics Of the Tensegrity Bridgementioning
confidence: 99%